Pengaruh Proses Rekrutmen, Seleksi, Dan Pelatihan Kerja Terhadap Kinerja Driver Online PT Gojek Indonesia Cabang Kota Malang - Nabilah Qotrunada; Rois Arifin; Andi Normaladewi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The purpose of this study was to determine the influence of the recruitment process, selection and job training on the performance of online drivers of PT Gojek Indonesia Malang City Branch. The data source of this research is primary data obtained from answers to questions when distributing questionnaires to online drivers of PT Gojek Indonesia Malang City Branch. The sample method used is Accidental Sampling. The number of samples in this study were 92 respondents. The data analysis method is using multiple linear regression analysis with classical assumption tests and statistical tests. The results showed: (1) the recruitment process has a significant effect on the performance of online drivers, (2) selection has a significant effect on the performance of online drivers, (3) job training has no significant effect on the performance of online drivers. Keywords: Recruitment Process, Selection, Job Training, and The Performance